Impact of wettability alteration on 3D nonwetting phase trapping and transport. (March 2016) - Herring, Anna L.; Sheppard, Adrian; Andersson, Linnéa; Wildenschild, Dorthe
Highlights: Bentheimer sandstone cores were treated to achieve different wettability states. 3D x-ray microtomography experiments characterize air and brine flow in the cores. Flow patterns during air invasion (drainage) are a function of wettability state. Residual trapping of air (after imbibition) is reduced in intermediate-wet cores. Buoyancy-driven flow becomes important for cores with altered wettability. Abstract: We investigate capillary trapping and fluid migration via x-ray computed microtomography (x-ray CMT) of nonwetting phase (air) and wetting phase (brine) in Bentheimer sandstone cores which have been treated to exhibit different degrees of uniform wettability. x-Ray CMT scans were acquired at multiple steps during drainage and imbibition processes, as well as at the endpoints; allowing for assessment of the impact of wettability on nonwetting phase saturation and cluster size distribution, connectivity, topology and efficiency of trapping. Compared with untreated (water-wet) Bentheimer sandstone, cores treated with tetramethoxylsilane (TMS) were rendered weakly water-wet, and cores treated with octadecyltrichlorosilane (OTS) demonstrate intermediate-wet characteristics. As apparent contact angle increases, drainage flow patterns deviate from those derived for water-wet systems, total residual trapping and trapping efficiency decrease, and buoyancy plays a larger role during nonwetting phase mobilization; this has significant implications for CO2 migration and trapping during CO2 sequestration operations.